Risk Factors, Complications and Immediate Outcome of Very Low Birth Weight Neonates in a level-III NICU (Bangladesh Critical Care Journal, 2021)
Background: Last two decades have witnessed a steady improvement in the quality of perinatal care in Bangladesh. Around 4-8% of all live births are very low birth weight (VLBW) & low birth weight (LBW)is 10.6%. The present study was done to determine risk factors, complications and immediate outcome in VLBW babies.Methods: It was a prospective cohort study conducted in a level-III NICU of Ad-din Hospital over two years period (April 2019-March 2021). 356VLBW babies (birth weight